Grotesque and paradox: Female and male narratives in Victor Erofeyev’s novels - Szabó, Tünde (Slavica, 2024)
This paper examines the narrative dynamics of two novels by Victor Erofeyev. The female discourse of Russian Beauty is characterized by the vertical dynamics of grotesque, while the discourse of the autobiographical narrator of Good Stalin is characterized by the dynamics of paradox, a horizontal movement between opposing truths. In both novels the Soviet aesthetic canon is undermined through the dynamics of narrative that denies the possibility of a singular truth.